PHENOL COMPONENT OF FRESH AND BOILED SEA GRAPES (CAULERPA SP.) FROM TUAL, MALUKU - Nurjanah Nurjanah; Agoes Mardiono Jacoeb; Diah Asih Asmara; Taufik Hidayat (University of Sultan Ageng Tirtayasa, 2019)
Caulerpa sp. commonly found in Tual, Southeast Maluku waters. Caulerpa sp. is generally consumed by coastal communities in it is raw form as salads or boiled. Nutrient information and total phenol compounds of Caulerpa sp. during boiling has not been reported. The aim of this study is to determine bioactive components and the levels of total phenol compounds Caulerpa sp. as a result of the boiling process. The boiling process is carried out for 5 minutes at 90 . Boiling process causes loss of flavonoids in Caulerpa sp. Total phenol compounds after boiling decreased by 11.76 mg GAE/g extract. Total phenolic of fresh Caulerpa sp. has better results than by boiling process.